ANALISIS UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH DARI PAJAK KENDARAAN BERMOTOR DI KOTA PALEMBANG - kusminaini Armin; Sahila Sahila (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
In order to increase Regional Original Income from Vehicle Tax in Palembang City. The data collection techniques used are observation, interviews, Library Research and documentation. The sample chosen by the author is Motor Vehicle Tax 2016 until 2018 in the city of Palembang using the purposive sampling method. From the results of the study that motor vehicle tax revenues seem to tend to decline, the causes are the low quality of the human resources of the tax apparatus, the weak supervision of motor vehicle taxes and the lack of awareness of taxpayers in paying taxes. From the analysis that motor vehicle tax revenue still does not meet the revenue target because the target setting is not quite right. The strategy that should be implemented is to increase the capacity of human resources for motor vehicle tax management. The contribution of motor vehicle tax in Palembang City shows that the contribution of motor vehicle tax is still above 30%, this indicates that motor vehicle tax is a large part of regional income through the regional tax sector.Keywords: Regional Original Revenue; Motor Vehicle Tax